Strengthening Teacher Competence in Building Motivation and Discipline for Learning Outcomes in MI - Didit Darmawan; Muchammad Bachrul Alam (Global Education Journal, 2026)
This study aims to analyze the model of teacher competence strengthening in building learning motivation and discipline to achieve meaningful learning outcomes in Madrasah Ibtidaiyah. Employing a qualitative literature review method with content analysis, this research synthesizes academic literature to develop a conceptual understanding of comprehensive teacher development models. The findings reveal that the model for strengthening teacher competence in building student motivation consists of needs-based training, intensive mentoring, structured reflection, professional learning communities, technology utilization, principal involvement, and impact evaluation. Teachers need to master motivation strategies including creating curiosity, providing appropriate challenges, positive reinforcement, connecting material to real life, creating enjoyable atmospheres, providing autonomy, and building positive relationships. The model for strengthening teacher competence in building learning discipline includes proactive classroom management training, positive reinforcement mentoring, effective communication skills, behavior function understanding, structured reflection, learning communities, parental involvement, logical consequences, positive classroom culture, role modeling, consistency, individual approaches, impact evaluation, and spiritual values ​​reinforcement. Both models together build the foundation for teachers to create motivating and disciplined learning environments that lead to meaningful learning outcomes. The study implies that teacher development programs must be designed as integrated models with intensive mentoring and sustainability.